PUBLIC HEALTH MEASURES AS AN EFFORT TO PREVENT AND CONTROL COVID-19 IN THE COMMUNITY: A LITERATURE REVIEW - Syamikar Baridwan; Agus Setiawan; Henny Permatasari (Jurnal Kesehatan, 2020)
On March 11, 2020, WHO declared the COVID-19 outbreak a global pandemic and it becomes an international concern and urged all countries to take action to detect viral infections and prevent spread. This study aims to explore various public health measures as an effort to prevent and control COVID-19. This study was conducted using a literature review method with descriptive analysis. Articles were obtained from online databases, namely Science Direct, Proquest, Sage Publication, SpringerLink and Google Scholar which were published in 2020. Various studies have shown that public health measures as an effort to prevent and control COVID-19 include washing hands using soap or portable hand sanitizer and avoiding face and mouth contact, wearing masks and avoiding close contact with sick individuals, social distancing and self-quarantine, and increasing contact testing and tracing capacity. The ability of community nurses is needed to provide and maximize community nursing care through health promotion.ABSTRAKPada tanggal 11 Maret 2020, WHO mengumumkan wabah COVID-19 sebagai pandemi global yang menjadi perhatian international dan mendesak semua negara untuk mengambil tindakan dalam mendeteksi infeksi virus dan mencegah penyebaran. Studi ini bertujuan untuk mengeksplorasi berbagai tindakan kesehatan masyarakat sebagai upaya pencegahan dan pengendalian COVID-19. Studi ini dilakukan dengan metode literature review dengan analisis deskriptif. Artikel diperoleh dari online database yaitu Science Direct, Proquest, Sage Publication, SpringerLink dan Google Scholar yang terbit pada tahun 2020. Berbagai penelitian menunjukkan bahwa tindakan kesehatan masyarakat sebagai upaya pencegahan dan pengendalian COVID-19 diantaranya mencuci tangan menggunakan sabun atau pembersih tangan portabel serta menghindari kontak dengan wajah dan mulut, menggunakan masker serta menghindari kontak dekat dengan individu yang sakit, social distancing dan self‐quarantine, serta meningkatan kapasitas pengujian dan pelacakan kontak. Kemampuan perawat komunitas dibutuhkan untuk memberikan dan memaksimalkan asuhan keperawatan komunitas melalui promosi kesehatan